Utilização de Pequi (Caryocar brasilienses Camb.) para produção sustentável de combustíveis e lubrificantes - Ferreira, Elano Nery (2019)
The main global energy sources are fossil fuels and these constitute as the main resources in the industrial area. However, environmental impacts have increased significantly in recent years due to the intense use of these resources. In this sense, the research aims to produce sustainable chemical derivatives from pequi oil as an alternative to mineral resources. For this, the raw material source was submitted two successive transesterification reactions via basic catalysis to produce biodiesel and pequi biolubricant. The chemical composition of fatty acids of pequi oil revealed by GC-MS analysis was 46.6% linoleic acid and 34.2% oleic acid. The work included a thermal and kinetic study of degradation in order to obtain the thermodynamic parameters to estimate the biodiesel activation energy. For biolubricant, a thermal study was carried out using thermal analysis coupled with infrared spectroscopy (TG-FTIR), an important analysis that qualifies the behavior of the material in the face of the many industrial and automotive applications. In order to measure the toxicity of the pequi biolubricant and to evaluate the addition this material in the NH10 mineral lubricant, the toxicity test was performed against the larvae of the microcrustacean Artemia salina. The acquisition of the biodiesel was confirmed by 1H and 13C NMR, characterizing a conversion of 88.9 ± 1.2%. Through thermogravimetric analysis, the biodiesel showed thermal stability of 176.70 °C at 10 °C min-1 showing a thermogravimetric profile similar to diesel type S10/B0. The average of the activation energy values obtained from the kinetic study for biodiesel was 67.07 kJ mol-1, these values being similar to those reported in the literature for diesel oil samples, suggesting pequi biodiesel as an alternative fuel. The obtaining of the pequi biolubricant was also confirmed by 1H and 13C NMR and showed characteristic signs that confirm the replacement of the hydroxyls of the TMP molecule by the fatty acid chains of the methyl ester. The TG-FTIR analysis showed three thermal degradation events for the pequi biolubricant, correlated the volatilization, oxidation in the unsaturation and combustion along molecule chain, respectively. The data from toxicity test against Artemia salina revealed low toxicity of the biolubricant and the study carried out to apply it as an additive in the NH10 mineral lubricant showed that the increase in the concentration of the additive reduces the harmful effects of the blends against the test organism, revealing its application potential.